SOSIALISASI PILKADA 2024 UNTUK MENINGKATKAN PARTISIPASI PUBLIK DAN PEMILU BERINTEGRITAS - Wirahadi, Umar; Raden Minda Kusumah; Itto Turyandi (Komunikasi, 2024)
The 2024 Regional Election socialization activity involving the Forum of Lecturer Communication (FKD) of West Java served as an interactive platform to address critical issues related to increasing public participation and ensuring electoral integrity. With a keynote speaker from the General Election Commission (KPU) of Bandung City, participants gained in-depth insights into the adverse effects of money politics on the quality of democracy. This discussion resulted in several strategic solutions, such as enhancing political literacy through the role of lecturers, strengthening community-based election monitoring, and utilizing technology for reporting violations.The collaboration between KPU, academics, and civil society was identified as a key element in overcoming challenges in the 2024 Regional Elections. FKD lecturers committed to leveraging their role as educators to disseminate the values of clean democracy to younger generations. The outcomes of this activity are expected to serve as a foundation for concrete actions supporting more transparent, participatory, and dignified elections, thereby contributing positively to the sustainability of democracy in Indonesia.